THE DETERMINANTS OF MALUS ON REGIONAL DEVELOPMENT BANK IN INDONESIA - Rana Syifa Medinda; Rahmat Febrianto (Universitas Multimedia Nusantara, 2023)
Abstract— This study is based on the Indonesian Financial Service Authority since 2015 regulates that banks must have a policy to defer, or to clawback, or combination of both the variable compensation paid to bank’s executive. Since the Indonesian Financial Authority allows banks to choose their compensation scheme, this study is to investigate the factors that influence the choice of the policy. Our study is among few studies that investigate this area because the regulation was enacted in 2017. Data are collected from Regional Development Bank in Indonesia that report their compensation policy since 2017 to 2019. We test financial and nonfinancial factors that may determine the choice of compensation policy. Banks with lower net interest margin tend not to choose malus. The similar conclusion is also given by the variable board of commissioner’s tenure. However, commissioner’s remuneration suggests a positive relationship with the propensity to choose malus other than other type of compensation policies. We find that net interest margin, board of commissioners tenure, and remuneration of executives are related to choice of clawback or malus. Future researchers may focus on the effect of corporate governance related to local governments-owned banks and remuneration provisions. Keywords: Clawback; Compensation; Corporate Governance; Holdback; Malus